2023
DOI: 10.3390/app13042499
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Configuration of an Order as an Integral Part of a Cyber-Physical System in a Manufacturing Operating According to Mass-Customisation Strategy

Abstract: The contemporary consumer market determines the use of mass customisation by manufacturers. Therefore, from the point of view of Industry 4.0 (I4.0), concept data and communications and analytics are relevant to the implementation of the mass-customisation strategy. The problem involves at least three subjects: how to connect the currently available information system within an enterprise with new I4.0 technologies, how new information solutions can support the verification of the feasibility of tailoring an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Integrating IT and operational technology ensures the production of correct variants, and individual order tracking facilitates the timely delivery of the finished product to customers. As shown in Table I, the findings of previous studies ( [9], [55], [57]- [62]) indicated that adopting ERP systems can effectively support the practical advancement of MC within firms from different industries. Firms should extensively use ERP systems to develop MCC.…”
Section: Facilitating Role Of Erp System In MCCmentioning
confidence: 93%
“…Integrating IT and operational technology ensures the production of correct variants, and individual order tracking facilitates the timely delivery of the finished product to customers. As shown in Table I, the findings of previous studies ( [9], [55], [57]- [62]) indicated that adopting ERP systems can effectively support the practical advancement of MC within firms from different industries. Firms should extensively use ERP systems to develop MCC.…”
Section: Facilitating Role Of Erp System In MCCmentioning
confidence: 93%